2018
DOI: 10.1186/s12906-018-2336-0
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study of the potential phytomedicinal use and toxicity of invasive Tithonia species in South Africa

Abstract: BackgroundTithonia diversifolia and T. rotundifolia belong to the Asteraceae family and are native to Mexico and Central America. These plants have become invasive in parts of tropical Africa and Asia where they have become an ecological, agricultural and economic burden. Tithonia diversifolia is exploited by locals in its native and most parts of its invasive range as a source of medicines; however, T. rotundifolia is only used for medicinal purposes in one country in the native range (Venezuela) and none in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…We chose the Vero cell line as an ideal in vitro model for the study because of its sensitivity to toxicity, ease to culture and readily available in our test facility. Additionally, it is recommended as a model to detect basal cytotoxicity (1,23,24). In this study, we set a threshold of the cytotoxic concentration (CC 50 ) below 20 µg/mL to be toxic, and above 20 µg/mL to be non-toxic as previously reported (1,21,22).…”
Section: Resultsmentioning
confidence: 99%
“…We chose the Vero cell line as an ideal in vitro model for the study because of its sensitivity to toxicity, ease to culture and readily available in our test facility. Additionally, it is recommended as a model to detect basal cytotoxicity (1,23,24). In this study, we set a threshold of the cytotoxic concentration (CC 50 ) below 20 µg/mL to be toxic, and above 20 µg/mL to be non-toxic as previously reported (1,21,22).…”
Section: Resultsmentioning
confidence: 99%
“…e assay was performed spectrophotometrically based on the formation of the complex Fe 3+ /xylenol orange according to Pinto et al [27] as previously described by Motlhatlego et al [28]. [29] as described by Omokhua et al [30]. From the previously reported MIC values [10,19] and lethal concentration 50 (LC 50 ) values obtained in the current study, the selectivity index (SI) values were calculated using the following formula: SI � LC 50 /MIC.…”
Section: Inhibition Of 15-lipoxygenase (15-lox) Enzymementioning
confidence: 99%
“…e genotoxicity evaluation of plant samples was done in the histidine-deficient growth medium using the Salmonella microsome assay according to Maron and Ames [31] as described by Omokhua et al [30].…”
Section: Genototoxicity Assaymentioning
confidence: 99%
“…On the other hand, T. diversifolia stands out as the most studied species, due to its widespread use in folk medicine. Several compounds of pharmacological and nutritional interest have been identified (Omokhua, Abdalla, van Staden, & McGaw, 2018).…”
Section: Morphological Characterizationmentioning
confidence: 99%
“…Although pharmacological activities associated with phytochemicals of T. diversifolia have in general been attributed to sesquiterpene lactones and, in some cases, to chlorogenic acid derivatives present in leaves, recent studies have shown that saponins and leaf flavonoids of T. diversifolia have potential pharmacological properties. However, future studies should be performed to substantiate such effects (Ajao & Moteetee, 2017;Omokhua et al, 2018). Research, Society and Development, v. 9, n. 10, e2339108370, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.8370…”
Section: Pharmacological Applications Of Tithonia Diversifoliamentioning
confidence: 99%